(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
The purpose of these lines is to remember the thought and character, in his adolescent years, of the outstanding academic José María Cadenas González, who died on May 6, 2019, through a kind of portrait of his life as an early thinker, between the beginning of the perezjimenista dictatorship, in December 1952, until the fall of the dictator and the beginning of 40 years of democracy in January 1958. I witnessed the beginning of his determined intellectual and university vocation, which led him to pursue an outstanding academic career in positions such as Dean of the Facultad de Humanidades y Educación, Vicerector Académico and Director of the Centro de Estudios de América in Universidad Central de Venezuela (UCV); as well as Academic Advisor to the Fundación Gran Mariscal de Ayacucho and other national and international higher education institutions.